(untitled) (Universal International Scientific Journal, 2026)
This review article analyzes the issue of developing students’ cognitive competencies in the context of inclusive physics education from a theoretical and practical perspective. The pedagogical and psychological foundations of inclusive education, the structural components of cognitive competence, and the specific didactic features of physics are summarized based on scientific sources. Also, the results of modern research conducted on the basis of differential and adaptive education, STEAM integration, information and communication technologies, and metacognitive strategies are analyzed, and scientific conclusions and recommendations are developed on optimizing the process of mastering physical knowledge in an inclusive environment, developing students’ logical and critical thinking, and forming an individual educational trajectory.